Price discovery on decentralized exchanges - CAPPONI, Agostino (Institutional Knowledge at Singapore Management University, 2024)
Decentralized exchanges (DEXs) allow traders to express their willingness to pay for quick execution through a public priority fee bidding mechanism. This influences the trading strategy of informed traders and creates a distinct price discovery process on DEXs compared to centralized exchanges. We present empirical evidence that high-fee DEX trades contain more private information. Informed traders bid high fees not only to avoid execution risk from blockchain congestion, but also to compete for execution priority. Using a dataset of Ethereum mempool orders, we demonstrate that informed traders employ a ``jump bidding'' strategy, placing high initial bids to deter potential competitors.